Study of the Microstructural Evolution in a 35Ni-25Cr-Nb Heat-Resistant Alloy by Dilatometry and Electron Microscopy - Sosa Lissarrague, Matías Humberto (2018)
The dendritic-type microstructure of the 35Ni-25Cr-Nb alloy, in the as-cast condition, consists of an austenitic matrix and two types of eutectic primary carbides; Nb-rich MC type and Cr-rich M23C6 type both present in interdendritic edges and grain boundaries. During aging at 1073 K for different times, M23C6-type secondary carbides precipitate in the matrix while MC-type carbides would transform into a Ni-Nb silicide, known as G-phase (Ni16Nb6Si7). The microstructure of this alloy was characterized by scanning electron microscopy with X-ray mapping, backscattered and secondary electron images, electron backscatter diffraction, and dilatometry, in order to detect the G-phase and analyze the conditions under which it is present. This undesirable silicide could reduce creep strength since Nb-rich carbide to G-phase transformation improves nucleation of microcracks in the interface between matrix and the silicide. Silicon and nickel were found on the edges of primary Nb-rich carbides in the as-cast condition. This could be indicating that the transformation of this carbide into Ni-Nb silicide is in an incipient stage and it probably occurs from the outside to the inside of the Nb carbide.